Sustainable Urban Development of the Slovak Republic - Douša, Milan (Bulletin of Geography. Socio-economic Series, 2021)
The concept of Sustainable Development as part of the EU agenda emphasizes the need for sustainability and the development of the economies of the EU Member States. The aim of the article is to evaluate the current state of selected activities defined as key for Sustainable Development, based on the analysis of the current state of selected Cities in the Slovak Republic. The article will propose recommendations based on the performed financial and economic analysis of selected transferred and original competencies of the cities of the Slovak Republic. The implementation of these recommendations will ensure the Sustainability of the Development of the cities in the Slovak Republic in the Future. This article is part of the solution of Project VEGA no. 1/0837/21 „Spatial and Temporal Aspects of EU Cohesion Policy: Lessons Learned and Future Perspectives“.